Analisis Faktor Pemicu Pencurian Harta Benda oleh Pemuda Kelompok Risiko di Wilayah Kecamatan Cengkareng Jakarta Barat - Rahmat Ibnu Joyo Kusumo; Amrizal (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The evolution of crime as a social phenomenon is influenced by a variety of factors, including politics, the economy, socio-culture, and efforts to survive. Theft of property poses a serious threat to society's peace and safety, particularly in the West Jakarta region, where cases of theft involving young people are frequent. The motivation behind this study is to recognize the triggers for burglary and plan powerful counteraction systems, zeroing in on in danger youth in Cengkareng, West Jakarta. Qualitative descriptive analysis was used to collect data from interviews and literature reviews. It is anticipated that this study will contribute to the creation of more efficient approaches to preventing crime in the region.The evolution of crime as a social phenomenon is influenced by a variety of factors, including politics, the economy, socio-culture, and efforts to survive. Theft of property poses a serious threat to society's peace and safety, particularly in the West Jakarta region, where cases of theft involving young people are frequent. The motivation behind this study is to recognize the triggers for burglary and plan powerful counteraction systems, zeroing in on in danger youth in Cengkareng, West Jakarta. Qualitative descriptive analysis was used to collect data from interviews and literature reviews. It is anticipated that this study will contribute to the creation of more efficient approaches to preventing crime in the region.